Pengaruh Brand Ambassador Lyodra Ginting terhadap Brand Awareness Konsumen Produk Implora : Survey Dilakukan Kepada Followers Akun Instagram @Lyodraofficial - Anita Rahmaan; Velda Ardia (Filosofi : Publikasi Ilmu Komunikasi, Desain, Seni Budaya, 2024)
Infuencer has a big impact on brands in order to improve their image to be more competitive with competitors, this is what Implora uses by using Lyodra's services as their Brand Ambassador, because Lyodra is considered to have Followers who is big and Lyodra himself is considered to have the appropriate charisma in the world of beauty. In this researchis to find out how much INFLUENCEBRAND AMBASSADOR LYODRA GINTING TOBRAND AWARENESS CONSUMERS OF IMPLORA PRODUCTS. The theory used is Brand Ambassador which includes Transference, Attractiveness, Congruence and Brand AwarenessUnware of Brand, Brand Recognition, Brand Recall, Top of Mind Data collection techniques were carried out by distributing questionnaires to 99 respondentsFollowers Instagram account @Lyodraofficial. Sampling using the techniqueProbability Sampling. Questionnaire retrieval method used namelyRandom Sampling. The results of this study indicate that InfluencePersonal Branding Lyodra Ginting as a whole responds well to respondents (Agree), as well as InfluenceBrand Ambassador Lyodra Ginting AgainstBrand Awareness consumers of Implora products (agree) from all statements from all X variables in the research questionnaire. In addition to the magnitude of InfluenceBrand Ambassador has a positive and strong relationship of 0.643 toBrand Awareness consumers of Implora productsFollowers Instagram account @Lyodraofficial with presentationBrand Awareness of 41.3% while the rest is influenced by other factors outside of this study. likeWord Of Mouth, other social media platforms and cosmetic product differences.